MDESRAP: a model for understanding the dynamics of electricity supply, resources and pollution - Qudrat-Ullah, Hassan (International journal of global energy issues, 2005)
The inherent dynamic complexity of the energy policy design problem makes the conventional "closed-form" solution impossible. This paper contributes a dynamic simulation model as a possible solution. The model captures the dynamics of underlying sectors of electricity demand, investment, capital, resource, production, environment and costs and pricing. The existing feedback loops, nonlinearity and time-lag characteristics present in the real world electricity systems are incorporated in the model. The model is calibrated to Pakistan's case data. How the model has been used in policy assessments and the design of the alternative energy policies subject to various environmental and resource constraints is also discussed.